Analysis of curtailment at The Geysers geothermal Field, California. (September 2020) - Dobson, Patrick; Dwivedi, Dipankar; Millstein, Dev; Krishnaswamy, Nandini; Garcia, Julio; Kiran, Mariam
Highlights: Annual curtailment at The Geysers between 2013–2018 ranges from 9 to 47 GW h. These levels are much lower than curtailment occurring in the late 1990s. Most curtailment events last a few hours in length. Power plants with the most curtailment are on a smaller (115 KV) transmission line. The Western Energy Imbalance Market has reduced curtailment. Abstract: Geothermal energy has traditionally been viewed as a baseload energy source, but the rapid growth of intermittent renewable energy has led to a need for more flexibility in power generation to avoid mandatory curtailment imposed by grid operators. This study of curtailment at The Geysers provides insights into the magnitude, duration, frequency, temporal and spatial distribution, and potential causes of curtailment events between 2013 and 2018. Annual levels of curtailment range during this period from 9 to 47 GW h, representing 0.15 to 0.81 % of the net generation. Most curtailments occurred at the power plants connected to a lower capacity transmission line and may result from transmission constriction. There is a clear link between negative pricing and economic curtailment, especially when solar production is higher. Economic curtailment events tend to be only a few hours and vary in magnitude up to almost 300 MW, whereas transmission-related curtailment events can be up to several weeks in duration. It is likely that curtailment of geothermal power will be an increasing concern, and could be mitigated by flexible generation strategies and increases in energy storage. It is critical to know the nature of curtailment events so that flexible generation options can be assessed properly.